1993
DOI: 10.1177/154193129303700305
|View full text |Cite
|
Sign up to set email alerts
|

Remote Conference Interpreting Using ISDN Videotelephone: A Requirements Analysis and Feasibility Study

Abstract: The introduction of videocommunications via the Integrated Services Digital Network (ISDN) offers the potential of significant changes in the working conditions of a variety of professions including conference interpreters. A study was conducted aiming at identifying the special videocommunications requirements of professional conference interpreters and establishing whether ISDN videotelephony offers a sufficient audio bandwidth and image resolution to support the interpreters in their work. To this aim, a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…2 What emerges from these studies is a tentative overall conclusion that even under extremely good technical conditions, conference interpreters who are not in the same location as the speakers experience more fatigue and stress and have a number of physiological and psychological complaints. While Böcker & Anderson (1993) and other earlier studies reported in Moser-Mercer (2005) and attributed such negative outcomes mainly to inferior technical conditions, Mouzourakis concludes that it has become clear that interpreter complaints were not only due to the inferior technological conditions, but also the result of a number of physiological (sore eyes, back and neck pain, headaches, nausea) and psychological complaints (loss of concentration and motivation, feeling of alienation) stemming from the remote interpreting conditions. These complaints resurfaced in subsequent experiments, conducted in a variety of technical conditions and by a number of multilingual organisations; it would thus be difficult to attribute them solely to a particular technical setup or even to the working conditions provided by a particular organisation.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…2 What emerges from these studies is a tentative overall conclusion that even under extremely good technical conditions, conference interpreters who are not in the same location as the speakers experience more fatigue and stress and have a number of physiological and psychological complaints. While Böcker & Anderson (1993) and other earlier studies reported in Moser-Mercer (2005) and attributed such negative outcomes mainly to inferior technical conditions, Mouzourakis concludes that it has become clear that interpreter complaints were not only due to the inferior technological conditions, but also the result of a number of physiological (sore eyes, back and neck pain, headaches, nausea) and psychological complaints (loss of concentration and motivation, feeling of alienation) stemming from the remote interpreting conditions. These complaints resurfaced in subsequent experiments, conducted in a variety of technical conditions and by a number of multilingual organisations; it would thus be difficult to attribute them solely to a particular technical setup or even to the working conditions provided by a particular organisation.…”
Section: Introductionmentioning
confidence: 80%
“…In an early experiment of this type, carried out by the European Telecommunications Standards Institute (ETSI) in co-operation with AIIC in 1992, a conference situation was simulated by presenting pre-recorded video material (speeches, debates) to the participating interpreters via an ISDN connection (cf. Böcker & Anderson 1993). In a joint project of the International Telecommunication Union (ITU) and the École de Traduction et d'Interprétation at the University of Geneva (ETI) in 1999 the technical feasibility of remote conference interpreting and its impact on human factors such as stress and fatigue were compared with traditional conference interpreting in a controlled-experiment, also using ISDNbased VC technology for the remote interpreting part of the experiment (cf.…”
Section: Introductionmentioning
confidence: 99%
“…In interpreting studies, subjective methods can provide data on: (i) how interpreters allocate attention; (ii) problem-solving strategies used by interpreters; (iii) the effect of interpreting expertise; and (iv) general assessment of cognitive activities in interpreting (i.e., comprehension, translation, and production; Ivanova, 2000 ). In early studies of DI, subjective methods were used to investigate how transmission techniques are used by interpreters ( Böcker and Anderson, 1993 ; Mouzourakis, 1996 , 2006 ; Jones et al, 2003 ). Among them, Mouzourakis (2006) reviewed the large-scale DI experiments that were conducted at the United Nations and the European Union institutions in which the subjective data collected by questionnaire were used to indicate how the technical setup for sound and image transmission would impact interpreters’ perceptions of DI.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…From the 1990s, a series of feasibility studies of video-mediated remote interpreting (in simultaneous mode) was organised by various institutions, including the European Telecommunications Standard Institute (ETSI) in 1993 (Böcker & Anderson 1993) Whilst the feasibility studies cited above involved comparisons of real-life or test performances in onsite and remote interpreting, a more recent study conducted by the Fraunhofer Institute for the Interpreting Service of the European Commission (SCIC) in 2010 aimed to define minimum standards for video and audio transmission in the context of remote simultaneous interpreting. This resulted in a comprehensive list of technological recommendations (Causo 2012).…”
Section: Ict-supported Interpretingmentioning
confidence: 99%